Evidentialism and its discontents - Dougherty, Trent (Oxford : Oxford University Press, 2011)
In this book, leading epistemologists challenge and refine evidentialism, the view that epistemic justification for belief is determined solely by considerations pertaining to one's evidence. Earl Conee and Richard Feldman, the leading advocates of evidentialism, respond to each essay in this engaging and illuminating debate.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Evidence; Knowledge, Theory of